2019
DOI: 10.1016/j.fitote.2019.104371
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing bioactive aporphine alkaloids as efflux pump inhibitors

Abstract: Extrusion of drugs or drug-like compounds through bacterial efflux pumps is a serious health issue that leads to loss in drug efficacy. Combinatorial therapies of low-efficacy drugs with efflux pump inhibitors may help to restore the activities of such drugs. In this quest, natural products are attractive molecules, since in addition to their wide range of bioactivities they may inhibit efflux pumps. The current work repurposed the bioactive alkaloid roemerine as a potential efflux pump inhibitor. In Bacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Growth curves obtained with increasing silibinin concentrations have shown that 25 µgmL -1 silibinin is suitable for testing its EPI feature since it did not alter growth. The antimicrobial berberine is widely known to be a substrate of a number of drug efflux pumps therefore its combination with different natural pump inhibitors may offer a way to enhance its efficacy (Avci et al, 2019;Stermitz et al, 2000). In order to evaluate the EPI property of silibinin, its combination with berberine has been tested on B. subtilis cells.…”
Section: Berberine and Silibinin Combinatorial Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Growth curves obtained with increasing silibinin concentrations have shown that 25 µgmL -1 silibinin is suitable for testing its EPI feature since it did not alter growth. The antimicrobial berberine is widely known to be a substrate of a number of drug efflux pumps therefore its combination with different natural pump inhibitors may offer a way to enhance its efficacy (Avci et al, 2019;Stermitz et al, 2000). In order to evaluate the EPI property of silibinin, its combination with berberine has been tested on B. subtilis cells.…”
Section: Berberine and Silibinin Combinatorial Treatmentsmentioning
confidence: 99%
“…In order to evaluate the EPI property of silibinin, its combination with berberine has been tested on B. subtilis cells. Berberine working concentration was determined based on previous work (Avci et al, 2019). In our previous work, 75 μgmL -1 berberine has been shown to only slightly affect B. subtilis 168 growth.…”
Section: Berberine and Silibinin Combinatorial Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several assays showed that roemerine potentiated the effect of berberine with MIC values reduced from 256 and 64 μg/mL and from 64 to 16 μg/mL, respectively, by inhibiting the Bmr efflux pump. In addition, transport assays conducted using E. coli inverted membrane vesicles overexpressing BmrA confirmed that increasing concentrations of roemerine inhibited the transport of the BmrA substrate, doxorubicin and through this pump [ 111 ].…”
Section: Alkaloidsmentioning
confidence: 99%